Contingent Negative Variation in the Evaluation of Neurocognitive Disorders Due to Possible Alzheimer’s Disease - Arquímedes Montoya-Pedrón; Carmen María Ocaña Montoya; Jorge Esteban Santos Toural; Tania Acosta Lee; Miguel Enrique Sánchez-Hechavarría; Erislandis López-Galán; Gustavo Alejandro Muñoz-Bustos (Neurology International, 2024)
The usefulness of Contingent Negative Variation (CNV) potential as a biomarker of neurocognitive disorders due to possible Alzheimer’s disease, is based on its possible physiological correlates. However, its application in the diagnostic evaluation of these disorders is still incipient. The aim of this study is to characterize the patterns of cognitive processing of information in the domain of nonspecific global attention, by recording potential CNV in a group of patients with neurocognitive disorders due to possible Alzheimer’s disease. An experimental study of cases and controls was carried out. The sample included 39 patients classified according to DSM-5 with a neurocognitive disorder subtype possibly due Alzheimer’s disease, and a Control Group of 53 subjects with normal cognitive functions. CNV potential was registered using standard protocol. The analysis of variance obtained significant differences in mean values and confidence intervals of total CNV amplitude between the three study groups. The late CNV segment amplitudes makes it possible to discriminate between the level of mild and major dysfunction in the group of patients. The CNV total amplitudes of potential allows for effective discrimination between normal cognitive functioning and neurocognitive disorders due to possible Alzheimer’s disease.